2007
DOI: 10.1074/jbc.m702988200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Silencing of TATA-binding Protein (TBP) by a Covalent Linkage of the N-terminal Domain of TBP-associated Factor 1

Abstract: General transcription factor TFIID is comprised of TATAbinding protein (TBP) and TBP-associated factors (TAFs), together playing critical roles in regulation of transcription initiation. The TAF N-terminal domain (TAND) of yeast TAF1 containing two subdomains, TAND1 (residues 10 -37) and TAND2 (residues 46 -71), is sufficient to interact with TBP and suppress the TATA binding activity of TBP. However, the detailed structural analysis of the complex between yeast TBP and TAND12 (residues 6 -71) was hindered by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Subsequent NMR structural studies using a single‐chain chimeric protein mimicking a protein–ligand complex have been reported (Candel et al. 2007; Mal et al. 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent NMR structural studies using a single‐chain chimeric protein mimicking a protein–ligand complex have been reported (Candel et al. 2007; Mal et al. 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Structure of the complex in the Ca 2+ -bound state Porumb et al (1994) initially showed that an engineered chimeric protein of calmodulin and the M13peptide appears to have high thermal stability and high binding affinity for Ca 2+ ions. Subsequent NMR structural studies using a single-chain chimeric protein mimicking a protein-ligand complex have been reported (Candel et al 2007;Mal et al 2007). Advantages of the chimeric protein for structural analysis include increased binding affinity of lowaffinity ligands and stabilization of protein-ligand complexes for long-term NMR measurements.…”
Section: Resultsmentioning
confidence: 99%
“…To circumvent this problem, we created fusion proteins, in which the two interacting partners are joined by a flexible linker. Fusion proteins enforce close proximity of the components of the complex, increasing the effective concentration and association rate and driving the binding process into the slow-exchange regime, thereby reducing line broadening and enhancing spectral quality (55,56). On the basis of the preliminary structure of the nontethered complex, we designed a fusion protein containing the TAZ2 domain of mouse CBP (residues 1764-1855) joined to the p53TAD (residues 2-61) by a six-residue Gly-Ser repeat sequence (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that an "active" fusion tag can also be highly effective. For example, Ikura and co-workers fused the TAF N-terminal Domain 1 and 2 (TAND12) with its binding partner TATA-binding protein (TBP) to form a stable protein complex, which displayed enhanced solubility and sample stability (Mal et al 2007). However, such an "active" fusion tag is target specific and cannot be easily applied to other proteins.…”
Section: The Set Should Not Interact With the Target Protein Or Protementioning
confidence: 99%